Toward A Redefinition of Management - Frew, David R. (Academy of Management Journal, 1971)
The article reports the author's opinions regarding the popular definition of management. He suggests that the popular job description for management, which incorporates tasks such as business planning, organizing, directing, and motivating, is limiting and inaccurate. The author proposes that a more accurate description of industrial management would include an element of goal-attainment.